Development of a small animal model for deer tick virus pathogenesis mimicking human clinical outcome - Hermance, Meghan E. (PLoS Negl Trop Dis, 2020)
Powassan virus (POWV) is a tick-borne flavivirus that encompasses two genetic lineages, POWV (Lineage I) and deer tick virus (DTV, Lineage II). In recent years, the incidence of reported POWV disease cases has increased, coupled with an expanded geographic range of the DTV tick vector, Ixodes scapularis. POWV and DTV are serologically indistinguishable, and it is not known whether clinical manifestations, pathology, or disease outcome differ between the two viruses. Six-week-old male and female BALB/c mice were footpad-inoculated with DTV doses ranging from 10(1) to 10(5) FFU. Dose-independent mortality, morbidity, and organ viral loads were observed for mice inoculated with sequentially increasing doses of DTV. By study completion, all surviving mice had cleared their viremias but detectable levels of negative-sense DTV RNA were present in the brain, indicating viral persistence of infectious DTV in the central nervous system. For mice that succumbed to disease, neuropathology revealed meningoencephalitis characterized by microscopic lesions with widespread distribution of viral RNA in the brain. These findings, coupled with the rapid onset of neurological signs of disease and high viral titers in nervous tissue, highlight the neurotropism of DTV in this mouse model. Additionally, disease outcome for DTV-infected mice was not affected by sex, as males and females were equally susceptible to disease. This is the first study to comprehensively characterize the clinical disease outcome in a small animal model across a spectrum of POWV/DTV infection doses. Here, we developed a small animal model for DTV pathogenesis that mimics the manifestations of POWV disease in humans. Since it is currently not known whether DTV and POWV differ in their capacity to cause human disease, the animal model detailed in our study could be utilized in future comparative pathogenesis studies, or as a platform for testing the efficacy of vaccines, and anti-virals.